2015
DOI: 10.1371/journal.pone.0143856
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Levels of Pro-Inflammatory Cytokines Released in the Vastus Lateralis Muscle of Patients with Fibromyalgia and Healthy Controls during Contractions of the Quadriceps Muscle – A Microdialysis Study

Abstract: ObjectiveFibromyalgia is associated with central hyperexcitability, but it is suggested that peripheral input is important to maintain central hyperexcitability. The primary aim was to investigate the levels of pro-inflammatory cytokines released in the vastus lateralis muscle during repetitive dynamic contractions of the quadriceps muscle in patients with fibromyalgia and healthy controls. Secondarily, to investigate if the levels of pro-inflammatory cytokines were correlated with pain or fatigue during these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 80 publications
5
60
2
Order By: Relevance
“…However, unlike the variability of results found in the blood of FM patients regarding IL-8 concentration, in the cerebrospinal fluid of these patients, it has only been found high concentrations of IL-8, a cytokine which promoving and mediating the pain [106,107]. As with other pro-inflammatory cytokines, we have not found reported differences in the concentration of IL-8 either on the muscle or on the skin of patients with FM [108,109]. IL-18, inflammatory cytokine closely related to the inflammasome function, was found elevated in the serum of patients with FM [83].…”
contrasting
confidence: 79%
See 3 more Smart Citations
“…However, unlike the variability of results found in the blood of FM patients regarding IL-8 concentration, in the cerebrospinal fluid of these patients, it has only been found high concentrations of IL-8, a cytokine which promoving and mediating the pain [106,107]. As with other pro-inflammatory cytokines, we have not found reported differences in the concentration of IL-8 either on the muscle or on the skin of patients with FM [108,109]. IL-18, inflammatory cytokine closely related to the inflammasome function, was found elevated in the serum of patients with FM [83].…”
contrasting
confidence: 79%
“…However, no differences were found in concentrations of TNF-α in skin of people with FM [108] or in muscle [109]. Although a recent study conducted by SanchezDominguez et al [35] have detected higher concentrations of TNFαin saliva and in the skin of FM patients when compared to healthy women.…”
Section: Cytokines In Fmmentioning
confidence: 87%
See 2 more Smart Citations
“…This result is not in line with other reports. For example, Wang et al found elevated levels of circulating TNF-α in FM, but no correlation between these levels and pain intensity [164], and Christidis et al did not find any difference between plasma levels of TNF-α between FM and controls and or any correlation with pain intensity [165]. In addition, more recently Ohgidani et al reported that protein levels and the expression of TNF-α at mRNA level significantly increased ATP-stimulated induced microglia-like cells in patients with FM compared healthy controls.…”
Section: Paper IIImentioning
confidence: 99%